Application Of The Analytical Hierarchy Process (AHP) And Simple Additive Weighting (SAW) Methods In The Selection Of The Best Employees At The Koperasi Simpan Pinjam Surya Kencana - Muhammad Satryandi Ogansyah; Anita Diana; Hestya Patrie; Bruri Trya Sartana (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2023)
Selection of the best employees is an important aspect, because it provides useful information for making human resources (HR) decisions such as promotions, training, bonuses, and other decisions. In addition, it is also important for the chairman of the board to formulate a mature policy to motivate employees. The obstacle to selecting the best employee at the Surya Kencana Savings and Loans Cooperative was that there was no selection of the best employee beforehand, so the chairman of the Cooperative management did not know the performance of his employees. The AHP method aims to get the weight value of each criterion. Then the SAW method which aims to classify values for each alternative based on predetermined criteria is used in the development of a decision support system. This study assesses the performance of the employees of the lending division at the Surya Kencana Savings and Loans Cooperative. By using the calculation of the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods, it will produce a performance value for each employee, so that the head of the cooperative can determine the best alternative, namely employees in the lending division. This research will produce a decision support system (SPK) that can recommend the best employees in the lending division of the Surya Kencana Savings and Loans Cooperative based on predetermined criteria such as attendance, targets, discipline, and collaboration with the AHP and SAW methods